Clinical manifestations of upper respiratory tract infection in children at Kalideres Community Health Center, West Jakarta - Widagdo, Widagdo; Mawardi, Harmon; Gandaputra, Ellen P; Fairuza, Firda; Pou, Rudy; Bukitwetan, Paul (Universa Medicina, 2007)
ntroduction The National Household Health Survey showed that the incidence of upper respiratory tract infection (URI) in Indonesia was high. The objectives of the study were to investigate the clinical manifestations of URI, its bacterial spectrum and sensitivity. MethodsA cross sectional study was carried out involving one hundred children with symptoms of URI i.e. fever, cough and or runny nose. The data of demography, physical sign, hematology, bacterial spectrum and sensitivity were collected. ResultsThe prevalence of URI was higher in male, younger age, smoker family, low educated, low income family, and polluted environment. The manifestations of URI were rhinopharyngitis (52%), pharyngitis (18%), rhinitis (12%), tonsilopharyngitis (10%), and tonsillitis (8%). The isolated bacteria were S. aureus, S. b hemolyticus, K. pneumoniae, C. diphtheriae, S. albus and S. anhemolyticus. S. aureus was higher in male than in female (p<0.01), while S. aureus, S. â hemolyticus, and C. bacterium diphtheriae were higher in preschool age children (p<0.01), and K. pneumoniae were higher in infants (p<0.01). S. aureus, and S. â hemolyticus were higher in children with under-nutrition, while in normal nutrition were of K. pneumonia and C diphtheriae (p<0.01). Most bacteria were intermediate and resistant to fourteen tested antibiotics.ConclusionThe manifestations of URI were rhinopharyngitis (52%), pharyngitis (18%), rhinitis (12%), tonsilopharyngitis (10%), and tonsillitis (8%), each of which could be associated with the complication and accompanying disease. The pathogenic bacterial spectrum of the throat consisted of S. aureus, S. â hemolyticus, K. pneumonia, and C. diphtheriae.